Allergens on desktop surfaces in preschools and elementary schools of urban children with asthma. Issue 7 (18th April 2014) - Kanchongkittiphon, W.; Sheehan, W. J.; Friedlander, J.; Chapman, M. D.; King, E.‐M.; Martirosyan, K.; Baxi, S. N.; Permaul, P.; Gaffin, J. M.; Kopel, L.; Bailey, A.; Fu, C.; et al.
Abstract Desktop dust has been studied as a source of food allergen, but not as a source of potential aeroallergen exposure. Thirty‐six wiped samples from desktop surfaces were collected from preschools and schools. Samples were analyzed for detectable levels of common aeroallergens including Alternaria, cockroach, dog, dust mite, cat, mouse, and rat allergens by immunoassay. Mouse allergen was the most prevalent, detectable in 97.2% of samples. Cat allergen was detectable in 80.6% of samples, and dog allergen was detectable in 77.8% of samples. Other allergens were not as prevalent. Mouse was the only allergen that was highly correlated with settled floor dust collected from the same rooms (r = 0.721, P < 0.001). This is the first study to detect aeroallergens on desktop surfaces by using moist wipes. Allergens for mouse, cat, and dog were highly detectable in wipes with mouse desktop surface levels correlating with levels in vacuumed floor dust.